MORPHOMETRIC OF THE COLORADO RIVER HIGH BASIN, ARGENTINA - Carolina Manuela Aumassanne; Fernanda Julia Gaspari; Maria Eugenia Bege; Paolo Daniel Sartor; Patricio Oricchio; Carlos Marcelo Di Bella (Boletín Geográfico)
The Grande and Barrancas Rivers watersheds conform the upper basin of the Colorado River. They provide discharge from snow precipitated in the high mountain peaks. Morphometric and functional characteristics analysis of a basin is elementary in hydrology and modeling approach. The aim of this work was to analyze and interpret the morphometric parameters and derived indices of the upper basin of the Colorado River, Argentina. Parameters quantification and analysis were based on a digital elevation model and Geographic Information Systems. Length of the Grande River is three times greater than Barrancas River ones, with a drainage area that follows the same relationship. Gravelius coefficients evidenced similarities in watershed shapes, both rectangled-oblongued. Both watersheds have a half of their area between 1500 and 2500 m.a.s.l., with predominant slopes between 0 and 15o. In both cases, 54% of slopes are orientated to south direction, meaning predominantly shady. Barrancas River has a greater difference between the source and the mouth, having a smaller drained area. Results from this study offers an important source of base information to further research and modeling spatio-temporal dynamics of flow of River basin.